Peran Guru dalam Pengelolaan Kelas untuk Mengoptimalkan Pembelajaran Sosiologi di SMA Taman Siswa Kodibangedo, Nusa Tenggara Timur - Marselinus Loghe Jaha; ST Ramlah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
This study focuses on teachers' roles and factors that impede teachers' role in classroom management at SMA Taman Siswa Kodi Bangedo in Southwest Sumba Regency to optimize sociology learning. The objectives of this study were to determine the teacher's role in classroom management to optimize sociology learning and the impediments factors in classroom management. The qualitative research method was employed in this study. To collect the data, the researcher used observation, interviews, and documentation. Besides, data reduction, data presentation, and data verification are the data analysis techniques. The study indicates that the teacher's role in classroom management was; as a learning designer, a learning manager, a motivator, a facilitator, a counsellor, and as a curriculum implementer. Theoretically, the teacher must master the class and its management as a whole so that the learning process can achieve its goals. Whereas the obstacle regarding the teacher's role not only comes from the teacher but also the students themselves, both from the family (parents) and school environment.